FACTORS INFLUENCING LOCAL BEAUTY PRODUCT REPURCHASE INTENTION - Veronica, Helen; Keni, Keni (International Journal of Application on Economics and Business, 2023)
The objectives of this study are to analyze and determine factors affecting repurchase intention of beauty products from local brands in Jakarta. The factors that will be analyzed for their influence on repurchase intentions include trust, word-of-mouth, and adjusted expectations. This study used a quantitative method by distributing questionnaires to 191 respondents who are the millennial generation living in DKI Jakarta and have at least bought and/or used local brand beauty product once in the past year. The collected 163 valid data is then processed using the PLS-SEM method with the SmartPLS statistical data processing tool. From this study, it can be concluded that trust, word-of-mouth, and adjusted expectations have a significant influence towards the repurchase intention of local brand beauty product consumers.